Cavβ1 regulates T cell expansion and apoptosis independently of voltage-gated Ca2+ channel function - Serap Erdogmus; Axel R. Concepcion; Megumi Yamashita; Ikjot Sidhu; Anthony Y. Tao; Wenyi Li; Pedro P. Rocha; Bonnie Huang; Ralph Garippa; Boram Lee; Amy Lee; Johannes W. Hell; et al. (Nature Communications, 2022)
The function of voltage-gated calcium channels in T cells is not well understood and controversial. Here the authors report that a regulatory beta subunit of voltage-gated calcium channels regulates T cell function despite no evidence that these channels were functional within T cells during activation.